The use of reverse transcription-PCR for the diagnosis of X-linked chronic granulomatous disease (2004)
ABSTRACT: Chronic granulomatous disease (CGD) is an inherited disorder of the innate immune system characterized by a defective oxidative burst of phagocytes and subsequent impairment of their microbicidal activity. Mutations in one of the NADPH-oxidase components affect gene expression or function of this system, leading to the phenotype of CGD. Defects in gp91-phox lead to X-linked CGD, responsible for approximately 70% of CGD cases. Investigation of the highly heterogeneous genotype of CGD patients includes mutation analysis, Northern blot or Western blot assays according to the particular case. The aim of the present study was to use reverse transcription (RT)-PCR for the analysis of molecular defects responsible for X-linked CGD in eight Brazilian patients and to assess its potential for broader application to molecular screening in CGD. Total RNA was prepared from Epstein B virus-transformed B-lymphocytes and reverse transcribed using random hexamers. The resulting cDNA was PCR-amplified by specific and overlapping pairs of primers designed to amplify three regions of the gp91-phox gene: exons 1-5, 3-9, and 7-13. This strategy detected defective gp91-phox expression in seven patients. The RT-PCR results matched clinical history, biochemical data (nitroblue tetrazolium or superoxide release assay) and available mutation analysis in four cases. In three additional cases, RT-PCR results matched clinical history and biochemical data. In another case, RT-PCR was normal despite a clinical history compatible with CGD and defective respiratory burst. We conclude that this new application of RT-PCR analysis – a simple, economical and rapid method – was appropriate for screening molecular defects in 7 of 8 X-linked CGD patients.